Regenerative medicine legislation in Japan for fast provision of cell therapy products. Issue 1 (20th November 2015) - Fujita, Y; Kawamoto, A
Abstract : A new legal framework consisting of three laws for cell‐based and tissue‐based therapies went into effect in November 2014 in Japan. Among the provisions of the laws, the Pharmaceuticals, Medical Devices, and Other Therapeutic Products Act (PMD Act) allows conditional and time‐limited approval for regenerative medical products based on the ensured safety and estimated efficacy in small‐scale clinical trials. The new legislation is expected to accelerate safe and fast provision of the innovative products to patients with intractable diseases.